Persepsi Kontraktor dan Konsultan Pengawas Pada Kinerja K3 Proyek Konstruksi di Surabaya - Harianto, Feri; Putri, Risca Amalia; Nuciferani, Felicia Tria; Choiriyah, Siti (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
Construction work has a high risk of work accidents. The high number of occupational accidents and illnesses makes evaluating K3 performance in construction projects necessary. The research aims to determine differences in perceptions between contractors and supervisory consultants regarding the K3 performance of construction projects. The research uses a survey method by distributing questionnaires to contractors (Project Manager, Site Manager, Site Engineer, and K3 officers) and supervisory consultants (Inspector, Chief Inspector, K3 officers, Quantity Surveyor, and Quantity Estimator). Respondents used purposive sampling, which amounted to 31 people. The analysis uses an independent t-test. The results of this research explain that in the work safety variable, five sub-factors show differences in perception between contractors and supervisory consultants. In the work environment variable, three subfactors show differences in perception. However, regarding the occupational health variable, the two groups had no difference in perception. In reality, contractors' perceptions regarding the maintenance of construction equipment most influence K3 performance. Meanwhile, the supervisory consultant's perception emphasized the importance of K3 implementation instructions, an organized layout of work facilities, and good lighting.